Retrieving the radical Tillich: his legacy and contemporary importance - Re Manning, Russell (Radical theologies, 2015)
"Paul Tillich (1886-1965) is best known today as a theologian of mediation. Fifty years after his death in 1965, for many Tillich has become an out-of-date thinker, a safe exemplar of a mid-twentieth-century theological liberalism. By contrast, from post-liberalism and Radical Orthodoxy to radical secular theologies, the current theological landscape is dominated by the notion of radicality. This collection shows forth Tillich as a radical theologian, strongly marked, but never fully determined by, the urgent critical demands of his time. From the crisis of a German cultural and religious life in ruins after the horrific defeat of the First World War, to the new realities of religious pluralism, Tillich's theological responses were always profoundly ambivalent, impure and disruptive, and never merely safely correlative. Far from the dominant image of Tillich as a liberal accommodationist in its place re-emerges the troubled and troubling figure of the radical Tillich"--